Biological Variables in Social Surveys - Rainer Schnell (Rat für Sozial- und Wirtschaftsdaten (RatSWD), 2010)
Social scientists have long virtually ignored the biological constraints of human behavior. Yet if the prediction of behavior is considered essential to a social science, neglecting any variable that might influence human behavior is unacceptable. This paper provides examples of important biological variables and describes their measurement in social surveys.
Keywords: 330